Using Human Rights Treaties to Resolve Ambiguity: the Advent of A Rights-Conscious Charming Betsy Canon - Waters, Melissa A (Victoria University of Wellington Law Review, 2007)
This article considers the role of international human rights law in the domestic context, and examines in particular the use of what the author calls a "rights-conscious Charming Betsy canon", whereby judges in New Zealand, Canada, the United States and Australia have interpreted statutory provisions (focusing on the case study of immigration law) so as to be consistent with international human rights norms. The author also considers the more radical use of the canon, proposed in particular by the High Court of Australia's Justice Kirby, which proposes that even constitutional texts may be interpreted to be consistent with international law, and discusses the threat this poses to traditional common law dualism.